Sustainability of the Village Owned Entrepises Program in Sumedang Regency, Indonesia: The Role of Government, Village Administration, and Voe Directors - Akadun, Akadun; Hidayat, Hidayat (Universitas Terbuka, 2025)
This study investigates the sustainability of Village-Owned Enterprises (VOEs) in Sumedang Regency, West Java, Indonesia, focusing on the roles played by central government agencies, village administrations, and VOE directors. Employing a qualitative case study approach, the research draws on in-depth interviews, document analysis, field observations, and focus group discussions to explore stakeholder influence on the implementation and longevity of VOE programs. The findings reveal that while government policies and funding schemes provide foundational support for VOE development, their sustainability is frequently compromised by inconsistent program implementation, political interference, underqualified management, and business models that do not align with local socio-economic contexts. In contrast, VOEs demonstrate greater resilience and long-term viability when managed by professional directors and supported through continuous institutional engagement. Given the urgent need to revitalize rural economies and reduce dependency on state aid, the study recommends targeted interventions such as salary subsidies for VOE directors and establishing Integrated VOE Units (VOETs) to enhance operational capacity and governance structures. This research contributes to the broader discourse on rural development and local economic empowerment by identifying critical gaps and practical solutions for strengthening VOE sustainability. The findings offer valuable insights for policymakers, local governments, and development practitioners aiming to foster inclusive and durable rural enterprise ecosystems in Indonesia and similar contexts.